2008
DOI: 10.1039/b712625e
|View full text |Cite
|
Sign up to set email alerts
|

Real wave packet and quasiclassical trajectory studies of the H++ LiH reaction

Abstract: Time-dependent real wave packet (RWP) and quasiclassical trajectory (QCT) calculations have been carried out to study the H(+) + LiH reaction on the ab initio potential-energy surface of Martinazzo et al. [J. Chem. Phys., 2003, 119, 11241]. Total initial state-selected and final state-resolved reaction probabilities for the two possible reaction channels, H(2)(+) + Li and LiH + H(+), have been calculated for total angular momentum J=0 at a broad range of collision energies. Integral cross sections and thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 26 publications
3
42
0
Order By: Relevance
“…25 along with our QCT results. For clarity, only the quantum results of Bulut et al are shown, since it was already shown that they agreed with the classical ones, 25 as is confirmed by our calculations. It is clear from this figure that (i) classical calculations are adequate in describing this reaction, as long as the resonance structure is of no concern, and (ii) the reaction does not show any threshold.…”
Section: Excited State Reactionssupporting
confidence: 87%
See 3 more Smart Citations
“…25 along with our QCT results. For clarity, only the quantum results of Bulut et al are shown, since it was already shown that they agreed with the classical ones, 25 as is confirmed by our calculations. It is clear from this figure that (i) classical calculations are adequate in describing this reaction, as long as the resonance structure is of no concern, and (ii) the reaction does not show any threshold.…”
Section: Excited State Reactionssupporting
confidence: 87%
“…25 is already available (and an analogous study is being published for the reverse reaction 40 ) we limit ourselves to show that our QCT results fully agree with those of ref. 25. This is shown in Fig.…”
Section: Excited State Reactionsmentioning
confidence: 78%
See 2 more Smart Citations
“…In a detailed study of the plausible lithium chemistry in the early universe, Stancil and coworkers (Stancil et al 1996) proposed that the LiH molecule may have contributed to the formation of the first condensed structures of the universe. Because of the potential astrophysical importance of the LiH molecule, the dynamical processes that lead to its destruction and formation have been the subject of several theoretical studies in recent years (Bulut et al 2008;Pino et al 2008;Wernli et al 2009;Bovino et al 2010Bovino et al , 2011Aslan et al 2012;Roy & Mahapatra 2012;Jiang et al 2013a). In this work, we focus on the theoretical study of the LiH + H → H 2 + Li (1)…”
Section: Introductionmentioning
confidence: 99%